Pemanfaatan Eceng Gondok dan Crude Palm Oil sebagai Bioaditif Bahan Bakar Kendaraan Bermotor - Wulanawati, Armi; Hairunnisa, Hairunnisa; Sinaga, Friska Wati; Islami, Yosianda Andusia (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
Eceng gondok contains chlorophyll which is an oxygenate type additive which can increase the combustion reaction in fuel and reduce exhaust emissions. Therefore, eceng gondok has the potential to be used as a bioadditive in fuel by adding carotene from crude palm oil which functions as an antioxidant through electron transfer, thereby protecting chlorophyll from autooxidation. The two chlorophyll and carotene extracts at a ratio of 0:1, 2:3, 3:1, 4:1, 3:2, and 1:0 respectively were mixed with toluene and Fatty Acid Methyl Ester as a bioadditive formula. in gasoline fuel. The research results show that there is an increase in octane value of 0.1-0.5% according to ASTM D 2699 and GC-FID and results in a reduction in CO and CO2 exhaust emissions of 52.38% and 37% respectively. .00% on the use of chlorophyll : carotene (2:3) bioadditives in gasoline. This shows that eceng gondok and crude palm oil can be used as bioadditives in gasoline motor vehicles.